Exploring the affective and cognitive dimensions of customer stickiness in deepfake platforms through the theoretical lens of attachment - Kanchan Patil; Dhanya Pramod; Vijayakumar Bharathi S; Dhoha AlSaleh (International Journal of Information Management Data Insights)
This study aims to understand how deepfakes affect customer stickiness, which characterizes the degree of customer retention on an online retail platform like Metaverse. Metaverse retail platforms can offer deepfake marketing to give customers an innovative buying experience. The study, built on the attachment theory and socio-technological approach, empirically evaluated affective and cognitive responses from 278 metaverse platform users using structural equation modelling. The results show that the technology factors, namely synchronicity, vicarious expression, and security and privacy, impacted platform attachment. The social factor, deepfakes interaction, impacted emotional attachment to deepfakes. The other social factors, deepfakes' familiarity and reputation, did not affect emotional attachment to Deepfakes' content. This study advances the literature on attachment theory and offers practical recommendations for retailers intending to explore deepfake usage on metaverse platforms. Our study proposes strategies for enhancing customers' attachment to retail brands through deepfakes and emphasizes the critical factors influencing customer retention in the context of metaverse retail.